Positive politeness strategies of Tonado Javaness (Jaton) community - Mojo, Julaiha Kyai; Tulung, Golda J.; Kalangi, Leika M. V.; Imbang, Djennie (Linguistics and Culture Review, 2021)
Politeness is very important in communication to maintain a harmonious relationship between the speaker and the speech partner and to avoid conflict. Politeness is a way to maintain and save the face of the speaking actor. A positive politeness strategy in speaking frankly with pleasantries is the speaker's effort in expressing polite behavior in the form of language. The focus of this research lies in positive politeness strategies in speaking frankly with pleasantries in the Tondano Javanese community. This study aims to describe and explain positive politeness speaking strategies used by the Tondano Javanese people who live in Kampung Jawa Village. This study uses a qualitative approach with a descriptive method. Data collection is done by listening, recording, and taking notes. Furthermore, the data were analyzed using the theory of politeness strategies by Brown and Levinson (1987), which is related to the concept of 'face'. The results show that the Tondano Javanese people use ten positive politeness strategies and these strategies are used in speech situations when the interlocutor is lower or equal in power to the speaker, and the relationship between the speaker and the speech partner is familiar.